Facial Nerve Palsy A Practitioner's Guide - Sanchetee, Pratap; Sachdeva, Kirti; Rajeshwari, R. (IntechOpen, 2022)
The 7th cranial nerve, commonly known as the facial nerve, is a compound nerve having motor, parasympathetic and sensory components. Its motor portion innervates muscles for facial movement and expression. Facial paralysis is a common clinical condition that significantly impacts a patient's quality of life. Clinical evaluation is the primary diagnostic tool, and advanced imaging techniques are usually not needed. While a majority of patients with Bell's palsy recover spontaneously, patients are generally treated with a combination of steroids, antiviral drugs, and physiotherapy. In this book, experts discuss recent advances in the diagnosis and management of 7th cranial nerve paralysis, along with surgical options.